A quantum-chemistry approach to the electro-oxidation mechanism of adsorbed carbon monoxide on platinum single-crystal clusters - Estiú, Guillermina (1990)
A molecular orbital interpretation of the electro-oxidation of CO adsorbed on Pt (100) and Pt (111) single-crystal clusters, based on the extended Hückel method, is presented. The metal surfaces are simulated with different (Pt)N clusters (N = 25 for Pt (100) and N = 19 for Pt (111)), and the influence of the applied potential is introduced by properly shifting the energy of the metal valence band. The multiplicity of the voltammetric peaks resulting for the reaction emerges from the potential-dependent stabilization energies of different ensembles of the type (Pt)N(CO)n(OH)m associated with the different CO coverages and coordination geometries. Data derived from the calculations indicate that only a linearly-bonded CO adsorbate appears to be most likely one involved in the electrochemical oxidative interactions.